A rapid and sensitive LC–MS/MS method for the determination of vanillic acid in rat plasma with application to pharmacokinetic study. (14th October 2021) - Liang, Yuan; Ma, Tiancheng; Li, Yuwei; Cai, Na
Abstract: Vanillic acid, a phenolic compound isolated from Angelica sinensis and green tea, exhibits excellent antioxidant and anti‐inflammatory activities. In this study, a rapid and sensitive ultra‐high‐performance liquid chromatography tandem mass spectrometry method was established and validated for the determination of vanillic acid in rat plasma. Plasma samples were prepared by protein precipitation with acetonitrile. Chromatographic separation was performed on a Zorbax RRHD Eclipse Plus C18 column (2.1 × 100 mm, 1.8 μm) with gradient elution at a flow rate of 0.3 ml/min, using mobile phase consisting of 0.1% formic acid (A) and acetonitrile (B). Vanillic acid and caffeic acid (internal standard, IS) were quantified by multiple reaction monitoring in negative ion mode. The method was fully validated according to the US Food and Drug Administration guidelines. The calibration curve was linear over the range of 2–1, 000 ng/ml with a correlation coefficient of >0.99. The carryover, matrix effect, extraction recovery, dilution effect, intra‐ and interday precision and accuracy were within acceptable limits. The method was then applied to a pharmacokinetic study of vanillic acid in rats. After oral administration at doses of 2, 5 and 10 mg/kg, the plasma concentration reached peaks of 0.42 ± 0.09, 0.73 ± 0.21 and 0.92 ± 0.28 μg/ml at the time of 0.55–0.64 h, respectively. The oral bioavailability was calculated as 25.3–36.2% in rat plasma. The result provided pre‐clinical information for further application of vanillic acid.